2013
DOI: 10.1002/adsc.201200449
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Oxidative Passerini Reaction of Alcohols Using a Magnetically Recyclable TEMPO under Metal‐ and Halogen‐Free Conditions

Abstract: A novel domino oxidative Passerini threecomponent reaction (OP-3CR) has been successfully developed with either primary or secondary alcohols instead of their corresponding aldehydes or ketones by using a recyclable magnetic core-shell nanoparticle supported TEMPO (2,2,6,6-tetramethyl-piperidin-1-oxyl) (MNST, 1). It has been shown that MNST is a highly effective and recyclable catalyst system in the metal-and halogen-free aerobic, oxidative, three-component Passerini reaction. To the best of our knowledge this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…This result also indicated that TEMPO was simply and conveniently attached to the particle surface Recently, Karimi and coworkers showed that TEMPO was linked to the surface of the aminopropyltriethoxysilanemodified magnetic nanoparticles through amide reduction using sodium cyanoborohydrides [29][30][31]. Another previously known example reported by Schätz et al [27] and Tucker-Schwartz and Garrell [28] is through "click" reaction using azide modified nanoparticles with TEMPO derivatives.…”
Section: Ft-ir Analysis and Elemental Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…This result also indicated that TEMPO was simply and conveniently attached to the particle surface Recently, Karimi and coworkers showed that TEMPO was linked to the surface of the aminopropyltriethoxysilanemodified magnetic nanoparticles through amide reduction using sodium cyanoborohydrides [29][30][31]. Another previously known example reported by Schätz et al [27] and Tucker-Schwartz and Garrell [28] is through "click" reaction using azide modified nanoparticles with TEMPO derivatives.…”
Section: Ft-ir Analysis and Elemental Analysismentioning
confidence: 89%
“…This approach combines a poly(acrylic acid) chain grafted from magnetic iron oxide nanoparticles and forms an ideal support material for 4-hydroxy-2,2 ,6,6 -tetramethylpiperidinyl-1-oxy (H-TEMPO). This novel method uses simple approaches and avoids potential harmful substances [27][28][29][30][31]; hence it is a facile and green approach to prepare iron oxide-based magnetic nanocomposite materials with efficient immobilization of TEMPO. The product was investigated as catalyst for alcohols/aldehydes or ketone transformation under both the Anelli [34] and Minisci [35] protocols.…”
Section: International Journal Of Polymer Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent this problem, the concept of generating the adequate carbonyl/imine electrophiles by means of the in situ oxidation of the corresponding alcohol/amine emerged. , As the first milestone in oxidative IMCRs, Zhu et al succeeded in performing an alcohol-based 3-component Passerini reaction by employing 2-iodoxybenzoic acid (IBX) as the stoichiometric oxidant (Scheme , eq (a)) . Whereas a catalytic version of this multicomponent process was later reported, , more attention was subsequently paid to oxidative 3-component Ugi–Joullié-type IMCRs, in which an amine or an aniline derivative serves as the imine/iminium precursor (Scheme , eq (b)). …”
Section: Introductionmentioning
confidence: 99%
“…22 , 23 As the first milestone in oxidative IMCRs, Zhu et al succeeded in performing an alcohol-based 3-component Passerini reaction by employing 2-iodoxybenzoic acid (IBX) as the stoichiometric oxidant ( Scheme 1 , eq (a)). 24 Whereas a catalytic version of this multicomponent process was later reported, 25 , 26 more attention was subsequently paid to oxidative 3-component Ugi–Joullié-type IMCRs, in which an amine or an aniline derivative serves as the imine/iminium precursor ( Scheme 1 , eq (b)). 27 41 …”
Section: Introductionmentioning
confidence: 99%